Overshoot Avoiding Control for Rigid Robots - Figen Özen (Turkish Journal of Electrical Power and Energy Systems)
Control of robots to ensure safe operation has been a current research topic ever since the manipulators were utilized in industrial applications. Humans and robots work together collaboratively more often these days. Providing a safer operation has become an issue that requires more attention. In this paper, the application of a control algorithm that combines a proportional plus derivative controller with an overshoot avoidance trajectory tracking mechanism is introduced. The operation of the algorithm is illustrated on a two-link planar manipulator. The performance is shown both by means of graphs of end effector trajectories and mean absolute error metric. The results indicate that depending on the gain of the proportional plus derivative controller, desired trajectories can be followed very closely and the error becomes negligibly small.